YouTube as a Source of Patient Information on Ankle Sprains: A Quality and Reliability Analysis - Jared Rubin; Alexander Tham; Michael Allen; Nathaniel Mattera; Nathaniel Mercer; Isaac Dayan; Jay Zaifman; Paloma Gauthier; John G. Kennedy (Journal of Sport Rehabilitation, 2026)
Context : Although ankle sprains are among the most common musculoskeletal injuries, prior studies have not systematically reviewed the educational quality of related YouTube videos. We aimed to evaluate the characteristics, sources, and educational quality of YouTube videos addressing ankle sprains. Design : Cross-sectional analysis of online material. Methods : We performed 4 independent YouTube searches on ankle sprains and recorded the top 25 results for each search. After screening 100 videos, we included 73 total videos for final analysis. We evaluated video content using 3 validated tools: Global Quality Scale (GQS), the Patient-Friendliness Scale, and the Journal of the American Medical Association criteria. Results : A total of 73 YouTube videos accumulated over 20.7 million views (mean: 283,546). Videos received 14.8 likes and 1.04 comments per 1000 views. Among included videos, the mean GQS score measured 3.75, Patient-Friendliness Scale score measured 3.48, and Journal of the American Medical Association score measured 1.19, indicating good accessibility, moderate educational quality, and poor transparency. Physicians produced the highest overall quality and transparency (GQS: 3.89, Journal of the American Medical Association: 1.50). Rehabilitation-focused content emerged as the most common theme (36%), maintaining good quality and accessibility (GQS: 3.77, Patient-Friendliness Scale: 4.23). Conclusion : YouTube offers wide access to ankle sprain information, yet video quality, accessibility, and transparency remain low. Physician-created and rehabilitation-focused videos demonstrated superior educational value, although highly viewed videos did not correspond with higher quality. These findings highlight the need for more reliable, high-quality ankle sprain content on online platforms.